ANALISIS KINERJA KEUANGAN PADA CITIBANK N.A., INDONESIA BRANCH DENGAN MENGGUNAKAN METODE CAMEL M - Maria. J. F. Esomar; Ayu Sukmadewi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
Financial Performance is a picture of the financial condition of a company.The purpose of this research is to assess the performance of the company by usingthe financial ratio analysis of Citibank N.A., Indonesia Branch. This researchconducted by performing the documentation technique with data which obtainedfrom financial statements Citibank N.A., Indonesia Branch ( 2011 – 2015) .Then is analyzed by using the analysis of financial statements whichconsist of Capital ratio, Earning Asset Quality, Management, Profitability andLiquidity (CAMEL). The analysis performed resulted in less ratio ratio onearning asset quality (RORA) and management (NPM) ratio, since the result ofthe value obtained did not meet the standard of bank soundness. Therefore, thereneeds to be more analysis for lending and control of costs. While the results of theratio of good ratio on capital ratios (CAR), rentability (ROA and BOPO) andliquidity (LDR).